Suicide Concern Reporting among Utah Youths Served by a School-Based Peer-to-Peer Prevention Program. Issue 1 (14th November 2018) - Wright-Berryman, Jennifer; Hudnall, Greg; Bledsoe, Cathy; Lloyd, Mary
Abstract: To date, no suicide behavior data related to school-based peer suicide prevention programs have been published. The Hope Squad program uses trained students to intentionally facilitate help-seeking with distressed peers. Suicide concern contact data (SCCD) from school counseling centers were collected from 2013 to 2017 as part of routine outcome-based program evaluation. Hope Squad school SCCD were organized by student gender, grade, and Hope Squad referral and were cross-tabulated with types of suicide concerns and hospitalizations. Over 1, 100 contacts ( N = 1, 174) across 65 schools in 41 school districts were included in the analysis. The highest rates of all suicide-related contacts were among girls and students in the eighth and ninth grades. Reported attempts peaked in the ninth and tenth grades, then reduced through the 12th grade. Nearly a quarter of all contacts were Hope Squad referrals. These descriptive data provide a general overview of the types and frequencies of Hope Squad school suicide concerns that present in school counseling centers and are not indicative of program effectiveness. Next steps will include a research study comparing outcomes between Hope Squad schools and non–Hope Squad schools, and a study examining implementation adherence using fidelity measures.